PEMANFAATAN MACROMEDIA FLASH 8 SEBAGAI MEDIA PEMBELAJARAN YANG INTERAKTIF BAGI GURU SMP METHODIST PEMATANGSIANTAR - Siagian, Gunaria; Situmorang, Masni Veronika; Silalahi, Mastiur Verawaty; Silaban, Winarto (Jurnal Pengabdian Bukit Pengharapan, 2025)
Amidst the rapid technological developments in today's digital era, the world of education is required to adapt to the use of technology-based media to support the learning process. One potential media to be used is Macromedia Flash 8, an interactive and engaging animation platform, highly relevant to support teaching skills activities. In facing the flow of disruptive innovation in the Industrial Revolution 4.0 era, educators need to improve their competencies, especially in the use of innovative and flexible learning technology. This community service activity was carried out through an educational approach, training, and direct mentoring to the participants. The stages of the activity include: 1) Providing education related to digital literacy and an introduction to the Macromedia Flash 8 application, 2) Training in creating animation-based learning content (starting from the planning stage, creation practice, to presentation of results), and 3) Mentoring and measuring participants' mastery of the media. The target of this activity is teachers at SMP Methodist Pematangsiantar. The activity was attended by four Biology education lecturers and 1 student from the Biology Education Study Program. Based on the evaluation results, 90% of participants stated that this activity was very helpful and provided new insights regarding the use of Macromedia Flash 8 in learning at school, especially biology learning, while the other 10% stated that this activity was useful and relevant to current learning needs